Understanding the Link between Intelligence and Lying - Michalis Drouvelis; Graeme Pearce (Center for Economic Studies and ifo Institute (CESifo), 2021)
Standard economic theory suggests that the decision to lie requires careful weighting of the associated economic costs and benefits, raising the question of whether intelligence matters for misbehaviour. Using the die roll paradigm, we compare behaviour between individuals who score either low or high on a Raven test when lying only benefits the subject who lies (Selfish treatment) or a charitable cause (Charity treatment). We find that high Raven individuals are honest in the Selfish treatment; however, their aversion to lying vanishes in the Charity treatment. Our results have important implications for the rapidly growing lying literature, indicating that intelligence is a key characteristic of misbehaviour.
Keywords: C90; Z13; 330; intelligence levels; die roll paradigm; honesty